Evaluation of temporary cement to prevent bacterial contamination of the root canal after pulpectomy - Letícia Martins PEREIRA; Sophia Maria Mateus NAVES; Júlia Modesto da COSTA; Igor de Oliveira MORAES; Sandra Regina Echeverria Pinho da SILVA; Carlos Eduardo FONTANA; Sérgio Luiz PINHEIRO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT To evaluate the ability of temporary cement (TC) and gutta-percha sticks (GP) to prevent bacterial contamination of the root canal through the coronal seal after pulpectomy. Eighty artificial primary maxillary central incisors were selected and randomly divided into 2 groups: TC (n = 40) and GP (n = 40). Endodontic access, rotary instrumentation, root canal filling, and coronal sealing were performed according to group allocation. The root canal opening was seeded with S. mutans and E. faecalis. Both groups were subdivided into 5 experimental time points (24, 48, 72, 96, and 120 hours), with 8 specimens per time-point group: 5 in which both root canal filling and coronal sealing were performed (with either TC or GP) and 3 controls (coronal sealing alone, without root canal filling). All specimens were incubated in an anaerobic jar at 37°C, and bacterial contamination was assessed in a spectrophotometer. ANOVA (t-test) was used to compare contamination and the Kruskal-Wallis test to compare filling scores between the experimental groups. A significant difference was observed in sealing in the first 24 hours between GP and controls (p = 0.046). There was no significant difference in the filling pattern between canals sealed with TC versus GP. Specimens sealed with GP showed less contamination than controls in the first 24 hours. At later time points, neither GP nor TC were effective at controlling bacterial contamination; both failed to provide adequate coronal sealing.